The Edinburgh history of reading : subversive readers - Rose, Jonathan, 1952- (Edinburgh University Press, 2020)
Subversive Readers explores the strategies used by readers to question authority, challenge convention, resist oppression, assert their independence and imagine a better world. This kind of insurgent reading may be found everywhere: in revolutionary France and Nazi Germany, in Eastern Europe under Communism and in Australian and Iranian prisons, among eighteenth-century women reading history and nineteenth-century men reading erotica, among postcolonial Africans, the blind, and pioneering transgender activists.
Keywords: Books and reading -- History.; Books and reading -- England -- History -- 18th century.; Books and reading -- England -- History -- 19th century.; Publishers and publishing -- England -- History -- 18th century.; Publishers and publishing -- England -- History -- 19th century.; Popular culture -- England -- History.; England -- Intellectual life -- History.; Authors and readers -- England.; Livres et lecture -- Histoire.; Livres et lecture -- Angleterre -- Histoire -- 18e siècle.; Livres et lecture -- Angleterre -- Histoire -- 19e siècle.; Culture populaire -- Angleterre -- Histoire.; Angleterre -- Vie intellectuelle -- Histoire.; Écrivains et lecteurs -- Angleterre.; Angleterre -- Vie intellectuelle.; LITERARY CRITICISM -- General.; Books and reading; Authors and readers; Intellectual life; Popular culture; Publishers and publishing; England; 1700-1899; History